PHYTOCHEMICAL, USE IN ETHNOMEDICINE, AND THERAPEUTIC ACTIVITIES OF MARCHANTIA GENUS - Purkon, Dicki Bakhtiar; Fadhlillah, Faizah Min; Maigoda, Tonny Cortis; Iwo, Maria Immaculata; Soemardji, Adreanus Andaja; Nadhifah, Ainun; Sudaryat, Yayat (Journal of Vocational Health Studies, 2022)
Background: Liverworts are a group of plants from the Marchantia genus containing various biologically active compounds and comprised of 65 species worldwide. This plant species belongs to the Marchantiaceae family, which was used empirically in China, North America, Ancient Greece, and Indonesia to treat open wounds, burns, hepatotoxicity, and infection prevention. Now, liverworts have great potential as medicinal and nutraceutical products because of their phytochemical content and diversity of pharmacological activities. Purpose: This review focuses on secondary metabolites obtained from the thalloid and whole plant parts (herbs) and the compilation of their pharmacological activities, which are still poorly documented. Review: This review article obtained related information through extensive international journals (online) scientific databases and offline (books) related to all searches of the species of the genus Marchantia which included: phytochemical content (secondary metabolites) and various pharmacological activities which were collected and compared all results of literature studies from various aspects. Some of the secondary metabolites are Marchantin A, B, D dan E; Paleatin B; Perrottetin F, and Plagiochin E, which have various pharmacological activities. Various results regarding all the therapeutic properties of the genus Marchantia have been produced in the world such as: antibacterial, antifungal, antioxidant, cytotoxic activity, anti-inflammatory, cardiotonic, hepatoprotective, muscle relaxant, antiosteoporosis, and skin care. Conclusion: Therefore, the potential for the development of medicinal, supplementary and nutraceutical products from various Marchantia species is very large and broad for the future.